2018
DOI: 10.1155/2018/9619684
|View full text |Cite
|
Sign up to set email alerts
|

Towards 90-90-90 Target: Factors Influencing Availability, Access, and Utilization of HIV Services—A Qualitative Study in 19 Ugandan Districts

Abstract: Background UNAIDS has set a new target 90-90-90 by 2020. To achieve this target, current programs need to address challenges that limit access, availability, and utilization of HIV testing and treatment services. Therefore, the aim of this study was to identify the barriers that influence access, availability, and utilization of HIV services in rural Uganda within the setting of a large donor funded program. Methods We conducted key informant interviews with stakeholders at the district level, staff of existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
6
24
0
2
Order By: Relevance
“…This observation remained significant in the stratified analysis for both female and male caregivers. This observation is consistent with many others which have established that lack of food is a significant barrier to ART utilization and adherence [14,55,[58][59][60]. People may be hesitant to start ART if they do not intend to stay on it due to such reasons as lack of food.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This observation remained significant in the stratified analysis for both female and male caregivers. This observation is consistent with many others which have established that lack of food is a significant barrier to ART utilization and adherence [14,55,[58][59][60]. People may be hesitant to start ART if they do not intend to stay on it due to such reasons as lack of food.…”
Section: Discussionsupporting
confidence: 91%
“…These disparities in ART use between male and female caregivers in the middle through fifth wealth quintiles were not clear, thus a need for further research to clarify the observed relationship. Overall, other studies have observed higher likelihood of ART use with better economic status [7,14,57,58,69].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations